Compatibility and Market Penetration of Family Takaful Product: A Comparative Study - Nor Haziah Hashim; Muhamad Muda (Universiti Sains Islam Malaysia, 2024)
This study aims to address the issue of low market penetration of family takaful products by assessing its compatibility in relation to their conventional competitors. Using comparative case studies approach, this study focuses on the Individual Family Takaful vis-a- vis Individual Life Insurance products. The purpose is to identify similarities and differences in product features, attributes and benefits. Based on this exploratory study, it can be concluded that in terms of product concepts, both takaful and the conventional products are quite compatible. However, the conventional products are more competitive, as they are able to provide varieties to the value added features. This study also concludes that takaful products need to be more competitive and innovative in order to cater for the increasingly sophisticated customers who demand more innovative products rather than the generic insurance product.